Microbiology of Urinary Tract Infection and the Status of Urinary Isolates in Pregnant Women - Parajuli, Sharmila; Thapa, B (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Urinary tract infection (UTI) is one of the most frequently encountered problems owing to significant number of patients needing hospitalization during pregnancy. The incidence of UTI in pregnant women is reported to be high up to 7-8%. Methods: This is a prospective study conducted in Valley Maternity Hospital during a period of 6 months (Jan 2011 to June 2011). 520 MSU (Mid stream urine samples) from pregnant women clinically suspected of urine infection were evaluated by urine dipstick analysis, microscopic and culture method. The isolates were identified and antibiotic sensitivity pattern was determined by standard protocol. Results: The majority of the patients were in-between the age group of 20-30years- 338cases (65%) and these patients usually presented in the first trimester of pregnancy- 317cases (60.96%). Out of the 520 clinically suspected UTI cases, 232 (44.61%) was culture positive. Out of the culture positive cases; Escherichia coli (E.coli) was the most common accounting for a total of 144cases (80%). Nitrofurantoin was found to be the most effective drug against the gram negative (Gm-ve) bacteria. Similarly, Ampicillin, Amoxycillin and Cloxacillin were found to be effective agent against gram positive (Gm+ve) bacteria. Conclusions: Screening for bacteriuria is recommended among all pregnant women at the first prenatal visit and in the subsequent trimesters of pregnancy. Prompt treatment of symptomatic UTI and asymptomatic bacteriuria is required in pregnant women to avoid complications like preterm birth, low birth weight and increased perinatal mortality.